Inequalities in the early detection of cervical cancer: a reality in the Costa Rica - Santamaría-Ulloa, Carolina (2021)
Introduction: Cervical cancer is one of the most common cancer types that affects the health of women worldwide. Objective: To determine if there are differences in the use of Pap smears at the regional level in Costa Rica, in order to visualize the inequalities related to the early detection of cervical-uterine cancer. Methodology. This study was conducted based on information from the 2014 National Household Survey. This survey is representative at the national level. R-Studio was used to estimate two multinomial regression models. The first one was used to explain the time that has elapsed since the last time women had a Pap smear. The second one was used to explain the reasons why women had never had a Pap smear. Data on the incidence of cervical cancer, from the National Tumor Registry of the Ministry of Health, were used in order to estimate the in-situ/invasive ratio. Results: Women who participate less regularly in screening are those residing in the Chorotega, Central Pacific and Huetar Caribbean regions. Compared to women in the Central region, women in these three regions are 80% (OR=1.80; p<0.01), 52% (OR=1.52; p=0.031) and 58% (OR=1.58; p<0.01) respectively more likely to have had a Pap screening 5 or more years ago, as compared to 1 to 2 years ago. Discussion: According to the results of this research, the Chorotega Region presents the most disadvantageous conditions in terms of the use of PAP, which represents a higher risk for women to develop lesions and cervical cancer. Conclusions: In order to reduce gaps and improve conditions of access to prevention, it is necessary to coordinate institutional efforts, both governmental and non-governmental, as well as the participation and protagonism of women.